Outcomes of adenoidectomy-alone in patients less than 3-years old. (March 2018) - Thadikonda, Kishan M.; Shaffer, Amber D.; Stapleton, Amanda L.
Abstract: Objectives: 1. Determine the percentage of patients under the age of 3 undergoing adenoidectomy-alone who require subsequent management of residual sleep disordered breathing (SDB).2. Characterize complications following adenoidectomy and determine if any perioperative factors are associated with intra-operative or post-operative complications and outcomes. Methods: Case series with chart review was conducted including children seen at a tertiary care children's hospital between 2008 and 2012. Consecutive patients under the age of 3 who underwent adenoidectomy-alone were identified by billing codes. After excluding those with syndromes, partial adenoidectomies, and those without follow-up, 148 patients were included. Predictors of requiring additional surgery for SDB were evaluated using log-rank tests or Cox proportional hazards regression. Results: Median age at time of initial adenoidectomy was 27.5 months (range 11–36 months) and the patient population was comprised of 66.2% males (n = 98/148) and 89.2% Caucasians (n = 132/148). 56.5% (n = 74/131) of patients continued to have residual symptoms of SDB and 34.5% (n = 51/148) underwent additional surgical intervention. Multivariable survival analysis revealed GERD (HR, 6.21; CI, 1.29–29.77, p = .022) and tonsil size (HR, 4.07; CI, 1.57–10.51, p = .004) were significant predictors of additional surgery in this group of patients under the age of 3. There was no observed difference in intra- and post-operative complication rates between patients with and without additional operative intervention. Conclusions: Residual SDB symptoms following adenoidectomy in patients less than 3 years of age are common and require additional surgery at a high rate. Medical comorbidities such as GERD and large tonsil size may help predict the need for additional surgery.